Stand up to stigma : how we reject fear and shame - Seele, Pernessa C. (Berrett-Koehler Publishers, Incorporated, 2017)
No More Hate! All Are Welcome! "Stigma" is a simple two-syllable word, yet it carries the weight of negative and often unfair beliefs that we hold about those who are different from us. Stigmas lock people into stereotyped boxes and deny us all the right to be our authentic and whole selves. Dr. Pernessa Seele, a longtime public health activist who started one of the first AIDS education programs in the 1980s, has crafted a proven method to address stigma. This powerful book confronts stereotype development, shows how to undo the processes and effects of stigma, and explains how we can radically change cultural thinking on the individual, interpersonal, and societal levels to put an end to stigmatization once and for all